Riki Mijling - Void/volume - Melissen, Antoon 1967-; Gomringer, Eugen 1925-; Lodermeyer, Peter 1962-; Floss, Kirsten (Kerber art, 2018)
Dutch sculptor Riki Mijling (*1954) works in a rich tradition of non-objective, (post-)minimalist sculpture. With her sculpture, and her works on paper too, Mijling has developed a unique visual language, pairing a reductive approach with a warm, "charged" character of her sculptures in waxed steel, Corten steel, stone and glass. The non-referential, archetypical forms of Mijling’s sculptures refer to basic principles of proportion and scale, to the universal significance of timeless forms. And unmistakably Mijling is the quest for a new experience of space. This richly illustrated publication contains essays by concrete poet and essayist Eugen Gomringer, Peter Lodermeyer and Antoon Melissen. Quelle: Verlag.